1995
DOI: 10.1071/pp9950927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Timing of Heat Stress During Grain Filling on Two Wheat Varieties Differing in Heat Tolerance. I. Grain Growth

Abstract: Short periods of very high temperature (> 35�C) are common in many of the world's wheat growing areas and can be a significant factor in reducing yield and quality of wheat. This study was designed to determine the stage at which grain growth is most sensitive to a short period of high temperature and to examine whether varietal differences in heat tolerance are expressed throughout the whole grain-filling period. Two varieties of wheat differing in heat tolerance (cvv. Egret and Oxley) were exposed to a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
98
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 22 publications
15
98
0
1
Order By: Relevance
“…For every 1 C above the optimal growing temperature of 15À20 C, the duration of grain filling was estimated to be reduced by 2.8 days in wheat (Streck 2005). However, slight increase in grain filling rates were not sufficient to compensate the losses caused by shorter grain filling periods (Stone and Nicolas 1995;Prasad et al 2008b). Similar results were observed with grain sorghum (Prasad et al 2006b(Prasad et al , 2008a.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…For every 1 C above the optimal growing temperature of 15À20 C, the duration of grain filling was estimated to be reduced by 2.8 days in wheat (Streck 2005). However, slight increase in grain filling rates were not sufficient to compensate the losses caused by shorter grain filling periods (Stone and Nicolas 1995;Prasad et al 2008b). Similar results were observed with grain sorghum (Prasad et al 2006b(Prasad et al , 2008a.…”
Section: Discussionsupporting
confidence: 74%
“…High temperature (40 C daytime maximum) during the early grain filling stage caused maximum decrease in individual grain weight; the negative effects became progressively less at later stages of grain filling (Stone and Nicolas 1995). Stone and Nicolas (1998) reported that a day of high temperature (40/21 C day/night) during grain filling decreased the individual grain weight by 14% compared with a control (21/16 C day/night).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar impact of heat on grain filling (i.e. GFD was affected with little effect on the grain filling rate) was observed by Stone and Nicolas (1995) after applying a similar heat treatment to ours (40 C : 19 C day : night at 15 DAA for 5 days). Sofield et al (1977) tested the effect of source supply on grain filling dynamics by subjecting wheat to three different light intensities during grain filling from 4 DAA onwards.…”
Section: Grain Growth and Developmentsupporting
confidence: 48%
“…Under similar treatment conditions, Tashiro and Wardlaw (1990) have reported that a treatment at 10 DAA was late enough to avoid producing any 'sterile', 'parthenocarpic', 'abortive' or 'shrunken'(wrinkly) wheat grains, but was not late enough to make some grains appear abnormal in other ways (notched, split or opaque). Such a treatment is still early enough to substantially reduce the final grain dry mass of susceptible varieties (Stone and Nicolas 1995). Pots were placed in trays of water to~2-cm depth while in the chamber to minimise drought stress.…”
Section: Experimental Design Plant Growth and Heat Stress Conditionsmentioning
confidence: 99%